"They say we are Criminals": The Stress, Fears, and Hopes of Migrant Dairy Workers as a Result of US Immigration Policies. Issue 5 (18th September 2020) - Becerra, David
ABSTRACT: Agricultural and dairy work is among the most dangerous work in the US. In addition to the dangers of work, undocumented migrant workers may face additional stress as a result of the increase in anti-immigration enforcement and criminalization of undocumented status. The purpose of the study was to better understand how migrant dairy workers were impacted by the increase in restrictive immigration policies and immigration enforcement, as well as how they coped with any issues they faced. Interviews were conducted with fourteen migrant dairy workers following the passage of several anti-immigration bills across the US. Findings revealed four major categories: three related to negative impacts of immigration policies and enforcement 1) fear, 2) stress and anxiety, and 3) perceptions of discrimination. An additional major category emerged that demonstrated the hope and resilience of participants in the face of an increasingly difficult socio-political environment. Implications for social service practice, policy, and research are discussed.